The development of a life annuity market in Australia: An analysis of supplier risks and their mitigation - Evans, John; Sherris, M. (Financial Services Institute of Australasia (Finsia), 2011)
The significant accumulation of superannuation assets must be converted into income to finance the retirement needs of individuals. This paper considers the development of a life annuity market in Australia focusing on the risk management for potential suppliers of long-term guaranteed annuity products. It also examines the role of government in this market, particularly in hedging for the major risks involved.